Realizing the Need for Digital Transformation of Stakeholder Management: A Systematic Review in the Construction Industry - Kristijan Robert Prebanić (MDPI AG, 2021)
The construction industry is among the least digitized industries, and the lack of innovation in construction project management practices has led to decreases in productivity. The European Directives for Public Procurement are pushing the entire construction supply chain towards more radical digital transformations over the next years, and project managers are left with the difficult task to harness ICT for the involvement and management of project stakeholders. Digitalization of various processes and practices used to manage stakeholders in construction projects is still low, and part of this problem lies in weak systematization of ICT systems which support these practices. Thus, this paper provides a systematic review of how digitalization and digital transformation affect the way stakeholders behave, engage, and communicate in projects. Following the PRISMA methodology, 73 sources from the literature were chosen for the final analysis. Results are presented through descriptive and qualitative content analysis. Six research topics were identified and thoroughly analyzed. Results show that BIM, social network analysis, and web-based applications as means to digitalize stakeholder management are more mature than social media and VR/AR. An important finding is the need to reengineer and digitally transform processes in construction projects and construction firms to enable further digitalization and effectiveness of digital technologies. Suggestions for further studies follow this line of thought.